ANALISIS ASSEMBLY LINE BALANCING UNTUK MENGOPTIMALKAN PRODUKSI PISAU DI PERUSAHAAN T. KARDIN PISAU INDONESIA - Alkadri Kusalendra Siharis; Imelda Junita; Budi Rahardjo (Universitas Tidar, 2019)
T. Kardin Pisau Indonesia Company is a company that produces handmade knives with employees who specialize in their work. The company is trying to optimize the production of its knives by minimizing idle time which will ultimately increase employee productivity. The existence of different levels of difficulty in the workmanship causes an imbalance of work time between employees. The purpose of this study is to illustrate the role of line balancing strategies to optimize knife production in the Indonesian Knife company. The strategy used is that each employee does a different job to finish and then helps the work of other employees who have not finished. Line balancing method is an activity that aims to move one task from one person to another, which in turn creates a balance of time between workers at one station and workers at other stations. The results showed that using this strategy obtained a level of production efficiency of 79.02% for process 1 and .79.48% for process 2.